2017
DOI: 10.1016/j.biomaterials.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3D in vitro metastasis model elucidates differential invasive strategies during and after breaching basement membrane

Abstract: Invasive breast cancer and other tumors of epithelial origin must breach a layer of basement membrane (BM) that surrounds the primary tumor before invading into the adjacent extracellular matrix. To analyze invasive strategies of breast cancer cells during BM breaching and subsequent invasion into a collagen I-rich extracellular matrix (ECM), we developed a physiologically relevant 3D in vitro model that recreates the architecture of a solid tumor with an intact, degradable, cell-assembled BM layer embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…Other current 3D spheroid models do not possess an intact, well‐formed basement membrane surrounding the spheroid. Most 3D models model the 3D microenvironment by mixing Matrigel and collagen I (Berens, Holy, Riegel, & Wellstein, 2015) or by using a mixture of agarose and Matrigel to from spheroids (Li et al., 2011)—or they form a thicker and more diffuse layer around the spheroids that is not organized into a discrete, thin sheet of basement membrane (Guzman, Sanchez Alemany, Nguyen, Zhang, & Kaufman, 2017). With the protocols in this article, collagen IV and laminin are observed by immunostaining to be co‐localized, with fibronectin decorating collagen I everywhere in the ECM hydrogel, surrounding the spheroid.…”
Section: Commentarymentioning
confidence: 99%
“…Other current 3D spheroid models do not possess an intact, well‐formed basement membrane surrounding the spheroid. Most 3D models model the 3D microenvironment by mixing Matrigel and collagen I (Berens, Holy, Riegel, & Wellstein, 2015) or by using a mixture of agarose and Matrigel to from spheroids (Li et al., 2011)—or they form a thicker and more diffuse layer around the spheroids that is not organized into a discrete, thin sheet of basement membrane (Guzman, Sanchez Alemany, Nguyen, Zhang, & Kaufman, 2017). With the protocols in this article, collagen IV and laminin are observed by immunostaining to be co‐localized, with fibronectin decorating collagen I everywhere in the ECM hydrogel, surrounding the spheroid.…”
Section: Commentarymentioning
confidence: 99%
“…With these caveats being raised, these results support the idea that multiple aspects of cancer cell migration are highly conserved across cancer types, and microenvironmental, casespecific factors might set the conditions for a more individual or collective migration by regulating cancer cell heterogeneity in terms of EMT and migration, as effectively represented by the variation of the parameters in the model. Supporting this picture, it has been recently shown that multiple breast cancer cell lines with varying origin and morphological features can switch from solitary to collective migration by manipulating the physical properties of the extracellular medium in vitro (40,41).…”
Section: Emt-induction In Nearest Neighborsmentioning
confidence: 94%
“…117 First, dispersed mammary epithelial cells and diluted rBM were seeded in a concave, low-adhesion well and centrifuged, causing them to self-assemble into a tumor spheroid with a rBM coating after 24 h (Figure 6C). Tumor spheroids were then embedded into collagen I.…”
Section: Enter the Matrix: Epithelial Morphogenesis And Disseminationmentioning
confidence: 99%
“…One advantage of engineered biomaterial platforms is their experimental accessibility relative to animal models, which is particularly useful for optical microscopy. In the publications highlighted here, fluorescence microscopy was utilized to reveal cell migration at the periphery, 87,89,109,115,117,118,150 distinct biomarker expression, 88 disorganization of epithelial architecture, 112,113,119,120,122124 as well as coordination between tumor and stromal cells. 128131,133 However, many of these publications utilized manual analysis of selected cells or tissues, which samples a limited subset of the population with low throughput.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation